Rejection of Cassation Application by The Supreme Judge Because The De-fendant Was Not Legally Proven To Have Committed A Criminal Act (Study Of Supreme Court Decision Number 2205k/Pid.Sus/2022) - Habibi NST, Muhammad Riski; Panjaitan, Budi Sastra (IHSA Institute, 2025)
The Supreme Court is the pinnacle of (legal) efforts in seeking justice through the judicial process, both as a cassation court and a court for judicial review. The Supreme Court in carrying out its judicial function does not always meet the expectations of justice seekers in particular, and the public in general. The method used in this writing is the normative legal approach method where the research conducted is by examining existing library materials (library research), which are related to the title being studied. The results of this study indicate that the Supreme Court's Cassation Decision No. 2205 K/Pid.Sus/2022, stated that it rejected the cassation from the Cassation Applicant/Public Prosecutor to the Corruption Eradication Commission, with the consideration that the Cassation Applicant/Public Prosecutor could not prove that the judex facti decision did not meet the provisions of Article 253 paragraph (1) letters a, b, c of Law Number 8 of 1981 concerning Criminal Procedure Law. The Public Prosecutor at the KPK filed an appeal in case number 2205k/Pid.Sus/2022, namely that 1) the reason for the Public Prosecutor's appeal was because the judex facti (District Court) was wrong in applying the law, the judex facti had tried the Defendant in the a quo case not in accordance with the applicable criminal procedure law, and the judex facti did not exceed its authority, 2) That the reason for the Public Prosecutor's appeal was basically regarding the judex facti not applying the law or applying the law improperly because the judex facti stated that the Defendant was proven to have committed a crime as charged by the Public Prosecutor.